Nuclear factor-?B expression in the endometrium of normal and overweight women with polycystic ovary syndrome - Koc, Onder; Ozdemirici, Safak; Acet, Mustafa; Soyturk, Ummugulsum; Aydin, Suleyman (Taylor & Francis Inc, 2017)
The aim of this study was to investigate whether the expression levels of endometrial NF kappa B p65 differ between normal weight and overweight PCOS women and to compare them with BMI-matched control subjects without PCOS. The study group comprised 20 normal weight (BMI: 18.5-24.9 kg/m(2)) and 15 overweight PCOS women (BMI: 25-29.9 kg/m(2)) with infertility. Healthy fertile women without PCOS were recruited as the control group. The patients in the normal weight PCOS group and control group were age and BMI-matched. Endometrial samples were obtained during the mid-luteal phase for immunohistochemical staining. The H-Score method was used to evaluate NF-kappa B p65 (Rel A) expression. Both normal and overweight PCOS women demonstrated significantly higher endometrial NF-kappa B p65 expression than the women without PCOS. The H-scores of endometrial NF-kappa B p65 expression were similar in both groups of PCOS women. NF-kappa B p65 was positively correlated with serum insulin, HOMA-IR and total testosterone levels in PCOS women. By leading to pathological inflammation, an increase in NF-kappa B p65 expression in the endometrium of normal and overweight PCOS women may contribute to PCOS-related subfertility. IMPACT STATEMENT What is already known on this subject: Although the pathogenesis of PCOS has not yet been clarified, low-grade chronic inflammation is gradually being established as an important pathogenetic factor. Increased levels of inflammatory cytokines such as IL-6 and TNF-alpha. have been reported in women with PCOS. Causes of pathological endometrial inflammation may arise from either a local endometrial disease or linked to diseases which are located in a distant reproductive tissue. Nevertheless, possible role of endometrial NF-kappa B, basic cellular regulatory of inflammation, in the pathophysiology of PCOS related implantation defect has not been elucidated yet. What do the results of this study add: This study provides first and novel insights into the relationship between PCOS related infertility and pathological endometrial inflammation. We demonstrated that there is a close association between PCOS and pathological endometrial inflammation. Moreover, we clearly showed that pathological endometrial inflammation occurs in both normal and overweight women with PCOS. Further, endometrial NF-kappa B p65 (Rel A) expression were found to be positively correlated with serum insulin levels and hyperandrogenism in overweight PCOS women. What are the implications of these findings for clinical practice: If we can analyse pathological endometrial inflammation by measuring endometrial NF-kappa B p65 (Rel A) expression, treatment could be directed towards eliminating the source of pathological endometrial inflammation.
Keywords: PCOS; nuclear factor kappa B; endometrial inflammation